Development Of Islamic Micro Finance In Bangladesh: A Review Of Literature - Md Faruk, Abdullah; Hossain, Biplob (2017)
Poverty is considered as a major problem of Bangladesh from the time when it has achieved independence. The government has already taken a number of initiatives to alleviate the poverty. However, Micro finance is one of the major programs which has been experienced a tremendous growth in last three decades. The aim of developing microfinance schemes is to provide employment opportunities for the poor in order to promote their financial health. Both conventional and Islamic modes are currently used to provide financing. However, many researchers believe Islamic mode of financing are more effective as it considers basic human needs. At present, Islamic Micro-Finance Institutions (IMFIs) are facing a number of challenges in Bangladesh due to its nature, lack of resources and regulatory support. However, this study is going to deliberate rationales behind the growth and development of Islamic Micro-finance industry in Bangladesh. Moreover, current challenges and possible suggestions of this industry are also discussed.